The Platelet-Endothelial Cell – VIII Axis - Nachman, R. L; Jaffe, E. A (Thrombosis and Haemostasis, 1976)
Cultured human endothelial cells synthesize and secrete a protein(s) which has factor VIII antigen and von Willebrand factor activity. Subcellular membrane and granule fractions derived from human platelets also contain the factor VIII antigen and von Willebrand factor activity. Circulating platelets constitute a significant reservoir of VIII antigen containing approximately 15 % of the amount present in platelet-poor plasma. Thus normal platelets contain surface bound as well as intracellularly stored von Willebrand factor, a protein synthesized by endothelial cells which is required for normal platelet function.